13 Pulmonary vein isolation- evaluating outcomes in the shift from radiofrequency to established cryoballoon ablation. (16th October 2019) - James, S; McCann, C; Cromie, N
Abstract : Background: Pulmonary vein isolation (PVI) is widely accepted as a valid therapeutic option for the management of paroxysmal atrial fibrillation where anti-arrhythmic drug therapy has failed. Radiofrequency (RF) catheter ablation is an established method of PVI. However, in recent years cryoballoon ablation (cryoablation) has been proven non-inferior to RF ablation both in terms of efficacy and patient safety. Purpose: Isolation of the pulmonary veins via cryoablation is increasingly popular. The primary aim of this study is to evaluate the initiation phase following implementation of the cryoablation technique in a previously RF ablation focused hospital. Methods: Comprehensive case note review was undertaken for 150 patients undergoing PVI. Analysis of outcomes was undertaken including intraoperative and postoperative complications, atrial fibrillation recurrence, as well as procedural data. Three subgroups were compared: 50 patients treated using RF catheter ablation The first 50 patients treated using cryoablation (learning phase) The following 50 patients treated using cryoablation (established phase) Results: The RF group vs the learning phase cryoablation group showed equivocal complication rate (4% vs 6%) but identified a much longer procedure time within the RF group (average time 211 mins vs 118 mins). Also shown is an increased AF recurrence rate among the learning phase cryoablation group (22% vs 36%) (table 1). As with previous studies; cryoablation is shown to be non-inferior to RF technique but with no superiority seen. A comparison between learning phase and established cryoablation shows significant improvement across all areas. Comparing the outcomes between RF and established cryoablation shows that PVI carried out by cryoablation took less than half the time of those carried out by RF (average time 211 mins vs 95 mins); radiation doses were subsequently smaller. Complication rates were also 0% for the established cryoablation group vs 4% for the RF cohort. AF recurrence rates were equivocal at 22% (RF) and 24% (established cryoablation). Conclusion: Procedural data from RF ablation and the learning phase of cryoablation show similar outcomes. Our study comparing the outcomes between RF and established cryoablation shows superiority of cyroablation in terms of procedural duration, radiation dose and complications whilst AF recurrence rates were equivocal. Hospitals which have not yet shifted to cryoablation should consider this when debating whether the proven benefits are worth the inconvenience and uncertainty of change.